Right to Employment Protection of the Adjunct and Internal Full Time Contract Faculties in the Tribhuvan Univer - Kandel, Deepak Raj (NPRC Journal of Multidisciplinary Research, 2024)
This study explores at the legal rules for recruitment part-time and full-time contract teachers at Tribhuvan University (T.U.) in Nepal. It focuses on how they are recruitment, selection, and how their rights are protected. The study uses legal documents like the T.U. Act and court cases from other countries to examine these issues. The findings show how T.U. uses part-time teachers, how it hires them, and how decisions made by the administration can affect them. The study also highlights international court cases to see what they say about following proper procedures, meeting contract obligations, and protecting the rights of teachers. Based on this, the study suggests ways to improve the situation, i.e., considering the needs of teachers, following labor laws, and having clear rules about academic freedom and job security. It also suggests making contracts clearer and giving teachers more rights, such as knowing more about their jobs and being able to bargain together as a group.